KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMPN 23 PEKANBARU - Meilia, Dessy; Razak, Abdul; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This research examines the ability to write text description of students of class VII SMPN 23 Pekanbaru. This study aims to find and describe the ability to write text description of students of class VII SMPN 23 Pekanbaru. This research is quantitative descriptive. The data of this research is the data of the result of doing the test (answer) the ability to write text description of the students of class VII SMPN 23 Pekanbaru. The instrument in this research is in the form of essay test about the ability to write text description of the students of class VII SMPN 23 Pekanbaru. Data collection is done by test technique. The population in this study as many as 143 students with the determination of a full sample of 105 students. Data were analyzed by quantitative descriptive method through kruskall wallis test. The validity of data is obtained through data validation method. The results of this study seen from the test of the ability to write text description of students class VII SMPN 23 Pekanbaru. Judging from the ability to write text description of the students of grade VII SMPN 23 Pekanbaru included in the medium category with an average value of 65.81.Keywords : Ability, Writing, Description Text